2015 IEEE 56th Annual Symposium on Foundations of Computer Science 2015
DOI: 10.1109/focs.2015.18
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Polynomials and Hamming Nearest Neighbors

Abstract: We show how to compute any symmetric Boolean function on n variables over any field (as well as the integers) with a probabilistic polynomial of degree O( n log(1/ε)) and error at most ε. The degree dependence on n and ε is optimal, matching a lower bound of Razborov (1987) and Smolensky (1987) for the MAJORITY function. The proof is constructive: a low-degree polynomial can be efficiently sampled from the distribution.This polynomial construction is combined with other algebraic ideas to give the first subqua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
148
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(151 citation statements)
references
References 26 publications
1
148
0
Order By: Relevance
“…Prior work showed OV is equivalent to Dominating Pair 6 [Cha17] and other simple set problems [BCH16]; our results add several interesting new members into the equivalence class. All problems listed above were already known to be OV-hard [Wil05, AW15,Rub18]. Our main contribution here is to show that they can all be reduced back to OV.…”
Section: An Equivalence Class For Sparse Orthogonal Vectorsmentioning
confidence: 99%
“…Prior work showed OV is equivalent to Dominating Pair 6 [Cha17] and other simple set problems [BCH16]; our results add several interesting new members into the equivalence class. All problems listed above were already known to be OV-hard [Wil05, AW15,Rub18]. Our main contribution here is to show that they can all be reduced back to OV.…”
Section: An Equivalence Class For Sparse Orthogonal Vectorsmentioning
confidence: 99%
“…Many of the problems below have been considered both in the field of algorithms on strings and in the field of computational geometry, and sometimes they are known under different Bichromatic closest pair with mismatches Ω(n 2−δ ) time ( [3,24]) Bichromatic closest pair with differences Ω(n 2−δ ) time ( [24], Corollary 6) Dictionary look-up with k mismatches Ω(n 1−δ ) query time ( [24]) Dictionary look-up with k differences Ω(n 1−δ ) query time ([24], Corollary 7)…”
Section: Related Work and Backgroundmentioning
confidence: 99%
“…For any δ > 0, there exists m = m(δ) such that SAT on m-CNF formulas with n variables cannot be solved in time O(2 (1−δ)n ). [3] showed that if there is δ > 0 such that for all constant c > 0, the bichromatic closest pair with mismatches problem, with d = c log n, can be solved in O(n 2−δ ) time, then SETH is false. By a standard reduction, this implies that no algorithm can process a dictionary of n strings of length d in polynomial time, and subsequently answer dictionary look-up queries with k = Θ(d) mismatches in O(n 1−δ ) time.…”
Section: ◮ Problem 4 Bichromatic Closest Pair With Mismatches (Diffementioning
confidence: 99%
“…Batch Setting. The study of the offline or batch setting for Nearest Neighbor Search has received renewed interest over the past years and has brought a wealth of techniques into light [40,2]. Given the connection between KDE and the Nearest Neighbor Search problem, it would be of practical and theoretical interest to design data-structures that offer provable speedups for the offline setting of the KDE problem.…”
Section: Data-dependent Hashingmentioning
confidence: 99%